2023
DOI: 10.1186/s10195-023-00702-w
|View full text |Cite
|
Sign up to set email alerts
|

Coronal alignment in total knee arthroplasty: a review

F. Matassi,
F. Pettinari,
F. Frasconà
et al.

Abstract: Total knee arthroplasty (TKA) alignment has recently become a hot topic in the orthopedics arthroplasty literature. Coronal plane alignment especially has gained increasing attention since it is considered a cornerstone for improved clinical outcomes. Various alignment techniques have been described, but none proved to be optimal and there is a lack of general consensus on which alignment provides best results. The aim of this narrative review is to describe the different types of coronal alignments in TKA, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…They concluded that the phenotype of the femoral component is not suitable to have a great variation [25]. At the same time, the tibial component is considered to be placed perpendicular to the tibial mechanical axis to ensure a balanced distribution of tibial loading and avoid concentration of shear forces [6,23]. As a result, the aMA and rKA strategies seem to be more suitable for Chinese OA knees than the MA, AA and KA strategies.…”
Section: Tka Bone Cut Strategies According To Functional Knee Phenotypesmentioning
confidence: 99%
“…They concluded that the phenotype of the femoral component is not suitable to have a great variation [25]. At the same time, the tibial component is considered to be placed perpendicular to the tibial mechanical axis to ensure a balanced distribution of tibial loading and avoid concentration of shear forces [6,23]. As a result, the aMA and rKA strategies seem to be more suitable for Chinese OA knees than the MA, AA and KA strategies.…”
Section: Tka Bone Cut Strategies According To Functional Knee Phenotypesmentioning
confidence: 99%
“…Finalmente, los alineamientos híbridos combinan principios de ambos enfoques sistemáticos y específicos para el paciente. 5,6 Estos métodos apuntan a mantener un ángulo cadera-rodilla dentro de una "zona de seguridad" que varía entre 177 y 183 grados, ofreciendo una solución intermedia que puede adaptarse a las necesidades específicas del paciente.…”
Section: Clasificación De Los Alineamientos Coronales En Prótesis Tot...unclassified
“…The coronal alignment in TKA has gained considerable attention. There are many different alignment principles, such as mechanical alignment (MA), anatomic alignment (AA), restricted kinematic alignment (rKA), adjusted mechanical alignment (aMA), and functional alignment (FA) [ 12 ]. However, sagittal alignment in TKA has been somewhat overlooked.…”
Section: Introductionmentioning
confidence: 99%